Elaboración de un sistema de manejo integral de los residuos sólidos urbanos para el cantón Cascales, Provincia de Sucumbíos - Salazar Alulema, Anthony Javier (2023)
This project is mainly oriented to analyze the current state of the integrated solid waste management system of the Cascales canton, Sucumbíos province focused on social, cultural, economic and environmental problems in order to make a proposal based on field studies and optimize the management of solid waste management. The methodology that was used was qualitative, field, descriptive, bibliographic research, since with them it was possible to achieve the proposed objectives such as characterizing the types of waste, evaluating the current system of the canton and designing a comprehensive management model for waste management. solid. The results obtained during the 3 weeks of sampling were a total of 3606.25 kg of garbage generated in the Cáscales canton, where the main waste is: plastic, cardboard, glass, paper, food remains, fruits and vegetables and the production per capita was 16.01% Kg/inhab/day.